Analisis Peran Instagram sebagai Media Promosi Kesehatan terhadap Literasi Kesehatan Mental Remaja - Ashifa Putri Mahira; Akrobi Imana; Rahmah Tussadiyah; Lingga Maya Putri; Hilmi Dzaki; Muhammad Al Zikra (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Mental health issues among adolescents have become an increasingly critical concern, particularly regarding the low level of mental health literacy among the younger generation. This study aims to analyze the role of Instagram as a health promotion medium in improving mental health literacy among adolescents aged 15–18 years. A descriptive quantitative method was employed using the Mental Health Literacy Questionnaire (MHLQ), which was distributed online to 70 respondents who met the inclusion criteria. The results indicate a significant positive correlation between the frequency of interaction with mental health promotion content on Instagram and adolescents' mental health literacy levels (ρ = 0.449; p < 0.05). Most respondents demonstrated moderate to high levels of mental health literacy, suggesting that Instagram has the potential to be an effective tool for enhancing adolescents' understanding and awareness of mental health issues. This study provides evidence that social media can serve as a non-formal intervention tool to support efforts in increasing mental health literacy among Indonesian adolescents.